Quantitative characterization of the housing of the elderly person mining from the 2013 PNAD - Natália Miguel, Eleusy; Caldas Tavares Mafra, Simone; Barroso Fontes, Márcia (Seven Editora, 2023)
The increase in life expectancy of the country’s population reflects directly on its demographic structure, causing significant changes to occur in the various population strata, especially in the elderly population. Housing for this population is an important factor, even because housing for the citizen is a physical and emotional need, that is, it is a fundamental question in your life. This article aims to present the housing characteristics experienced by the elderly population of Minas Gerais. To this end, we opted for a descriptive research with secondary data from the PNAD 2013 (IBGE). Both the extraction and the entire data processing and analysis process were performed using the statistical program STATA – Data Analysis and Statistical Software, version 12.0 . It was concluded that the elderly population of Minas Gerais lives in their own houses made of masonry and covered with slabs or tiles, and they are served with basic sanitation and appliances, such as a stove and refrigerator. DOI: 10.56238/pacfdnsv1-032